REJUVENATING SCRIPT FORMAT: THE USE OF EMOJI IN SCRIPTWRITING (A CASE STUDY ON "KENAPA GUE?" IN OTT VIDIO SERIES) - Baskoro Adi Wuryanto; Eurico Kevin Pratama (LAYAR: Jurnal Ilmiah Seni Media Rekam, 2023)
ABSTRACT This research explores the rejuvenation of script format through the innovative incorporation of emojis in scriptwriting. Despite their widespread use in digital communication, emojis have not been conventionally integrated into film scripts. This study aims to investigate the strategic use of emojis as visual elements to enrich communication and evoke emotions effectively in the film narrative. A key case study analyzed in this research is the Indonesian web series, "Kenapa Gue?", produced by Vidio Originals. This series dominantly capture lives on computer and smartphone screens, adeptly weaving together various digital platforms to craft a captivating mystery. Emojis play a pivotal role in "Kenapa Gue?" by visually conveying character emotions and enhancing the authenticity of dialogue. Through an in-depth examination of the impact of including emojis in scripts, this study examines the potential benefits and challenges. By conducting surveys and analyzing the case study, we explore how the creative integration of emojis fosters a more engaging and collaborative environment during production, ultimately elevating the film narrative. This research introduces a novel perspective on scriptwriting, highlighting the seamless blend of emojis with contemporary storytelling. By advocating for the inclusion of emojis as expressive tools within scripts, this study positions emojis as valuable assets in the film industry, rejuvenating the art of scriptwriting and elevating cinematic expression. In conclusion, this study bridges the gap in conventional scriptwriting practices, inspiring filmmakers and scriptwriters to harness the communicative power of emojis. Embracing emojis as an integral part of the script format unlocks exciting possibilities for invigorating storytelling in the digital age, making it a key catalyst for modern cinematic innovation. ABSTRAK Penelitian ini mengeksplorasi peremajaan format naskah dengan adanya pemakaian emoji dalam penulisan naskah. Meskipun penggunaannya luas dalam komunikasi digital, emoji belum diintegrasikan secara konvensional ke dalam naskah film. Penelitian ini bertujuan untuk menyelidiki strategi penggunaan emoji sebagai elemen visual untuk memperkaya komunikasi dan membangkitkan emosi secara efektif dalam narasi film. Studi kasus utama yang dianalisis dalam penelitian ini adalah serial web berbahasa Indonesia, “Kenapa Gue?”, yang diproduksi oleh Vidio Originals. Serial ini secara dominan menampilkan kehidupan di layar komputer dan ponsel pintar, dengan lihai merangkai berbagai platform digital untuk menciptakan sebuah misteri yang menawan. Emoji memainkan peran penting dalam "Kenapa Gue?" dengan menyampaikan emosi karakter secara visual dan meningkatkan keaslian dialog. Melalui kajian mendalam mengenai dampak penyertaan emoji dalam skrip, penelitian ini mengkaji potensi manfaat dan tantangannya. Dengan melakukan survei dan menganalisis studi kasus, dieksplorasi bagaimana integrasi kreatif emoji menumbuhkan lingkungan yang lebih menarik dan kolaboratif selama produksi, yang pada akhirnya meningkatkan narasi film. Penelitian ini memperkenalkan perspektif baru tentang penulisan naskah, menyoroti perpaduan antara emoji dan pengisahan cerita kontemporer. Dengan menganjurkan penyertaan emoji sebagai alat ekspresi dalam naskah, penelitian ini memposisikan emoji sebagai aset berharga dalam industri film, meremajakan seni penulisan naskah, dan meningkatkan ekspresi sinematik. Kesimpulannya, penelitian ini menjembatani kesenjangan dalam praktik penulisan naskah konvensional, menginspirasi pembuat film dan penulis naskah untuk memanfaatkan kekuatan komunikatif emoji. Menggunakan emoji sebagai bagian integral dari format naskah, membuka kemungkinan menarik untuk memperkuat penyampaian cerita di era digital, menjadikannya hal utama bagi inovasi sinematik modern.